216k views
2 votes
Let a and b be positive integers. 23^a x 23^b

User Cleptus
by
5.7k points

2 Answers

5 votes

Answer:

23^(a+b)

Explanation:

A^x*A^y = A^(x+y)

you can think of it like this

A^x = A*A*A*.......*A x times

A^y = A*A*A*....*A y times

therefore A^x * A^y = A*A*A*...*A (x+y) times

=A^(x+y),

so in our case A = 23, and x and y were a and b, so 23^a * 23^b = 23^(a+b)

User Ganesh Kaspate
by
5.3k points
5 votes

Answer:

23 ^ ( a+b)

Explanation:

23^a *23^b

Since the bases are the same, we can add the exponents

23 ^ ( a+b)

User Egdmitry
by
5.6k points